Nível de implantação das práticas obrigatórias e recomendadas de governança eletrônica no âmbito do poder executivo dos estados brasileiros e Distrito Federal - Braga Neto, José Garrido (2013)
The corporate governance involves a set of strategies used to manage the relationship between the principal and the agent, bringing impacts to the organization’s management and performance. In the governmental context, it is also possible to identify a relationship like that: between the citizen (principal) and the public manager (agent). Thus, this research picks up as main theoretical platforms the agency theory and public choice theory. The importance of agency theory to public governance is verified because the citizen needs keep up with the actions realized by the government, to ensure that public decisions are focused in the people interests. The lack of knowledge about public management induces to information asymmetry between the government and society that is not always properly knows the modus operandi of the government. Based on the theory of public choice, the government should take decisions aimed to the society demands, and not to get own achievement, opposite benefit to the public interest. A good public governance structure can contribute to the public choices endorse the increase of the people welfare state and not the care managers' personal interests, as well as soften the negative effects produced by information asymmetry. To avoid these problems, the government should approach its relationship with society and the development of information technology tools help in this task, in particular through the use of the internet, which also assists in the transparency and accountability. In recent years, the practices of electronic governance have gained ground on the government goals. Several studies have sought to identify a set of practices that represent good governance in the public sector through the virtual media. Still these studies have yearned to list determinants of public management which have impacts on electronics transparency, aspect of electronic governance picked up by this research. Therefore, the main objective of this research is to investigate the level of implementation of required and recommended practices of electronic governance, under the executive power of the Brazilian States and the Federal District. The research is characterized as descriptive, conducted through document analysis and a qualitative data approach. The population comprises the governments of the 26 Brazilian states and the Federal District. The secondary data were obtained and analyzed between the November 2012 and April 2013. Based on the investigations, it was found that none of the Brazilian States have performed all practices of electronic governance. Furthermore, the level of attendance of required practices was greater than that seen in recommended practices. The results of the required practices are considered poor, since it was assumed by the research the full identification of these practices, because of requirements of the law. The results about recommended practices are unsatisfactory too, because it was expected to identify all practices, so partial or total. The results corroborate the statements about the agency theory and the public choice theory. The States with the highest implementation levels of practices offered conditions to verify the progress of the public policy through the Internet and also facilitated access to public services through virtual media. This contributes to reduction of informational asymmetry about government management and enables the people to exercise the social control. In other hand, the results less expressive glimpsed the absence of mechanisms for stimulating popular participation through virtual media, hindering the control of public accountability and decisions making of managers, focusing on the welfare of the population.